THE GEOLOGICAL HERITAGE OF THE LOWER JURASSIC OF CENTRAL PORTUGAL: SELECTED SITES, INVENTORY AND MAIN SCIENTIFIC ARGUMENTS (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2004)
The Lower Jurassic is well represented in west-central Portugal (Lusitanian Basin), where several outcrops with exceptional exposures exist. Among these, three sites have a major interest for Geological Heritage: S. Pedro de Moel, Rabaçal and Peniche. These localities display important sections for the study of the Liassic carbonate successions, whose scientific and educational value, for the domains of Palaeontology, Stratigraphy, Sedimentology and Geomorphology is widely known. The aim of this work is to enumerate the main scientific arguments for considering these Portuguese Liassic localities as national and international relevance and as an important heritage value (Geosite).